Thermal optimization and comparison of geometric parameters of rectangular and triangular fins with constant surfacing - Bunjaku, Florent (Strojniški vestnik, 2017)
This paper presents an optimization model of fins of rectangular and triangular profiles, based on a constant value of the transverse cutting surface, as well as the optimization of the ratio of efficiency of both fin profiles. The optimization model is based on the analytical and numerical simulation of the heat flux through fins in order to derive relevant thermo-physical parameters of the investigated fin profiles. The optimization of both fin profiles is carried out for different fin materials based on constant heat transfer coefficient and for different fin materials based on variable heat flux. The efficiency of fins as relevant fin goodness parameter is also analysed and the optimal values of the ratio of fin efficiency of both profiles is graphically presented and the optimal value estimated. Numerical simulation of fin models is carried out by using ANSYS/Fluent software.
Keywords: geometrijski parametri; optimizacija; pravokoten in trikoten profil; rebra; toplotni tok; učinkovitost reber